The dead lands : a novel - Percy, Benjamin (Grand Central Publishing, 2015)
In the post-apocalypse, folks getting by in the Sanctuary (the remains of St. Louis) are surprised when a woman rushes in to report that in the West, civilization flourishes and crops grow. Unfortunately, there's also an army on the march that enslaves everyone it encounters.